Melatonin confers cadmium tolerance by modulating critical heavy metal chelators and transporters in radish plants. Issue 1 (15th May 2020) - Xu, Liang; Zhang, Fei; Tang, Mingjia; Wang, Yan; Dong, Junhui; Ying, Jiali; Chen, Yinglong; Hu, Bing; Li, Cui; Liu, Liwang
Abstract: Cadmium (Cd) is an environmental pollutant that causes health hazard to living organisms. Melatonin (MT) has emerged as a ubiquitous pleiotropic molecule capable of coordinating heavy metal (HM) stresses in plants. However, it remains unclear how melatonin mediates Cd homeostasis and detoxification at transcriptional and/or post‐transcriptional levels in radish. Herein, the activities of five key antioxidant enzymes were increased, while root and shoot Cd contents were dramatically decreased by melatonin. A combined small RNA and transcriptome sequencing analysis showed that 14 differentially expressed microRNAs (DEMs) and 966 differentially expressed genes (DEGs) were shared between the Cd and Cd + MT conditions. In all, 23 and ten correlated miRNA‐DEG pairs were identified in Con vs. Cd and Con vs. Cd + MT comparisons, respectively. Several DEGs encoding yellow stripe 1‐like (YSL), heavy metal ATPases (HMA), and ATP‐binding cassette (ABC) transporters were involved in Cd transportation and sequestration in radish. Root exposure to Cd 2+ induced several specific signaling molecules, which consequently trigger some HM chelators, transporters, and antioxidants to achieve reactive oxygen species (ROS) scavenging and detoxification and eliminate Cd toxicity in radish plants. Notably, transgenic analysis revealed that overexpression of the RsMT1 ( Metallothionein 1 ) gene could enhance Cd tolerance of tobacco plants, indicating that the exogenous melatonin confers Cd tolerance, which might be attributable to melatonin‐mediated upregulation of RsMT1 gene in radish plants. These results could contribute to dissecting the molecular basis governing melatonin‐mediated Cd stress response in plants and pave the way for high‐efficient genetically engineering low‐Cd‐content cultivars in radish breeding programs.